Defiance, Persuasion or Conformity? The Argument in Plato’s Apology and Crito - Domaradzki, Mikołaj (Peitho. Examina Antiqua, 2011)
The present paper attempts to throw some light on the conundrum of Socrates’ political views in the Apology and Crito. The problem resides in that the Socrates of the Apology evidently undermines the authority of Athenian democracy, whereas the Socrates of the Crito argues that his escape from prison would be tantamount to disrespecting the state, which would in turn threaten the prosperity of the entire πόλις. The article suggests that in the two dialogues, the young Plato examines the possibility of steering a middle course between embracing relativism, on the one hand, and encouraging civil disobedience, on the other. Thus, the philosopher focuses primarily on investigating the two options, without either totally subordinating the citizen to the state, or unreflexively accepting any crude pragmatism.